Peran Restoran Garuda Dalam Mendukung Wisata Kuliner Halal di Kota Medan (Studi Kasus : Restoran Garuda Jl. H. Adam Malik No. 14 Medan) - Chair, Marsari; Yusrizal, Yusrizal; Nasution, Juliana (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Looking for a halal restaurant or restaurant is a must for Muslim visitors, because one proof of obedience to Allah's commands is to eat halal food and not eat unclean food. The large number of restaurants or restaurants in Medan that provide non-halal food makes Muslim tourists or Muslim visitors confused about choosing a halal restaurant. Finding halal food in the city of Medan is not difficult, because the ethnic population of Medan is Malay, most of the Malays are Muslims. One of the restaurants in Medan with the characteristics of Minang-Malay cuisine is "Garuda Restaurant". This study aims to find out and analyze the efforts that have been made by Garuda Restaurant in supporting halal culinary tourism in the city of Medan. Then to find out and analyze the business that will be carried out by the Garuda Restaurant in supporting halal culinary tourism in the city of Medan and to find out and analyze the obstacles faced by the Garuda Restaurant in supporting halal culinary tourism in the city of Medan. This study uses a qualitative approach with qualitative descriptive research methods through interviews and supported by documentation conducted to the Head of the Garuda Restaurant Services Division, Jl. H. Adam Malik No. 14 Medan regarding the role of the Garuda Restaurant in supporting halal culinary tourism in the city of Medan. The results of the study show that there are several efforts that have been made by the Garuda Restaurant in supporting halal culinary tourism in the city of Medan, starting from maintaining quality, how to market to customers, holding promos, and providing complete facilities at the Garuda Restaurant. The efforts that will be carried out by the Garuda Restaurant in supporting halal culinary tourism in the city of Medan are to improve the quality of service to the community and improve the quality of the products being marketed. Apart from that, there are obstacles faced by Garuda Restaurant in supporting halal culinary tourism in the city of Medan, namely the operational time limit and the many other restaurant competitors.